Video in Listening Comprehension Test : Is It Valid, Reliable And Practical Enough ? - Aulia, Muhammad (JURNAL SERAMBI ILMU, 2011)
The paper addresses the use of video in listening comprehension test. There are still debates on this medium though all strongly believe that bringing real life communication into a language education is one succeeding indicator to accelerate positive development of language learners. The method used is test usefulness as a synthesis conceptual framework to determine validity, reliability, practicality, authenticity, ethics and professionalization related to the test. There is no final answer through this paper in deciding whether this multimedia is the best way to capture language features and to assess test-takers ability. Nevertheless, at least, this paper examines the medium and brings up some aspects considered for better language testing and assessment method in future.